2019
DOI: 10.1371/journal.pone.0223376
|View full text |Cite
|
Sign up to set email alerts
|

The views and experiences of general dental practitioners (GDP’s) in West Yorkshire who used the International Caries Detection and Assessment System (ICDAS) in research

Abstract: ObjectiveTo explore, through face to face interviews with a selection of General Dental Practitioners (GDPs), their views and experiences of having used the International Caries Detection and Assessment System (ICDAS) within primary care research studies for recording caries.MethodsThis qualitative study involved one on one interviews with eight GDP’s who had previously used ICDAS on patients in their dental practices as part of a research study. The participants were selected from among those who had taken pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…The present results may, however, reflect the general culture of the dental discipline [ 20 ]. Furthermore, the reward system of dentists has not generally been based on recording activity but on other measures than recording diagnoses and this may modify the actions of dentists [ 19 , 21 ]. Fortunately, the situation is changing.…”
Section: Discussionmentioning
confidence: 99%
“…The present results may, however, reflect the general culture of the dental discipline [ 20 ]. Furthermore, the reward system of dentists has not generally been based on recording activity but on other measures than recording diagnoses and this may modify the actions of dentists [ 19 , 21 ]. Fortunately, the situation is changing.…”
Section: Discussionmentioning
confidence: 99%
“…After a thorough evaluation of the existing literature [11,15,16], a topic guide was created for this study, which was then content validated by a dental public health specialist. Suitable candidates were emailed participant information sheets and requested to contact the research team if they were interested in participating in the study.…”
Section: Participants Recruitment and The Interview Processmentioning
confidence: 99%
“…Previously published data on ICDAS has mostly centred on establishing the index's reliability, reproducibility, validity, and accuracy [9,10]. In a research of West Yorkshire dentists' perspectives and experiences [11], it was discovered that dentists experienced various hurdles in applying it, including a lack of simplicity, financial constraints, and time limitations. Nevertheless, study exploring the barriers faced by clinicians and researchers in using the ICDAS index is still scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies exist comparing these systems to gold standards for lesion activity, one study found an accuracy of 52% for dentists determining lesion activity using IC-DAS [Cotta et al, 2015]. Moreover, general practitioners find these systems too complicated, time consuming, and costly to use in practice and thus their utilization is low [Khattak et al, 2019]. In real-world practices, identification of severity, particularly early lesions, and lesion activity is likely worse than being reported in the literature with these systems.…”
Section: Introductionmentioning
confidence: 99%